2020
DOI: 10.1039/d0sc03061a
|View full text |Cite
|
Sign up to set email alerts
|

Metal–ligand bond strength determines the fate of organic ligands on the catalyst surface during the electrochemical CO2 reduction reaction

Abstract: Colloidally synthesised nanocrystals (NCs) are increasingly utilised as catalysts to drive both thermal and electrocatalytic reactions. Their well-defined size and shape, controlled by organic ligands, are ideal to identify the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…97 In contrast, a recent paper from Buonsanti et al showed complete removal of native phosphate and trialkylamine ligands from the surface of Cu 0 nanospheres. 98…”
Section: Resultsmentioning
confidence: 99%
“…97 In contrast, a recent paper from Buonsanti et al showed complete removal of native phosphate and trialkylamine ligands from the surface of Cu 0 nanospheres. 98…”
Section: Resultsmentioning
confidence: 99%
“…The research used Cu nanoparticle as benchmark catalysts to investigate the effects of capped different organic ligands (Fig. 9 f) (i.e., oleylamine (OLAM), oleic acid (OLAC), dodecanethiol (DDT), trioctylphosphine (TOP), trioctylphosphine oxide (TOPO), and tetradecylphosphonic acid (TDPA)) on the CO 2 RR activity [ 204 ]. The selection of ligands is based on the following three reasons, i.e., wide range of applications, varied binding strength derived from different functional groups, and a typical research case for studying the correlations between catalytic activity and ligand surface coverage.…”
Section: Interface Engineering For Co 2 Rrmentioning
confidence: 99%
“…h Changes in the charge-transfer resistance (R CT ) over time for CuNCs capped by different ligands. Reprinted with permission from Ref [204].…”
mentioning
confidence: 99%
“…In some reactions, the real active center comprises single metal atoms with functional ligands, as well as well‐defined surfaces [211–212] . The ligand may control the oxidation state, geometry, and d n electron configuration of the metal center, [212] contributing significantly to the activity, selectivity, and stability of catalysts [213–219] . Depending on the ligands and supports attached to the center metal, the performance of prepared SACs may vary substantially [220–221] .…”
Section: Understanding Of Active Centermentioning
confidence: 99%
“…[211][212] The ligand may control the oxidation state, geometry, and d n electron configuration of the metal center, [212] contributing significantly to the activity, selectivity, and stability of catalysts. [213][214][215][216][217][218][219] Depending on the ligands and supports attached to the center metal, the performance of prepared SACs may vary substantially. [220][221] Taking Pt SACs as an example, powdered MgO, Al 2 O 3 , and CeO 2 were used as supports to anchor a Pt single atom with a ligand 3,6-di-2pyridyl-1,2,4,5tetrazine (DPTZ).…”
Section: Single Atom With Ligands and Supportsmentioning
confidence: 99%